2009
DOI: 10.1007/s00534-009-0127-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of residual in situ carcinoma on postoperative survival in 125 patients with extrahepatic bile duct carcinoma

Abstract: Purpose: The aim of this study was to determine the impact of the presence of carcinoma in situ at the bile duct stump on postoperative survival in patients who underwent resection of extrahepatic bile duct carcinoma. Methods:The patients with resected extrahepatic bile duct carcinoma were divided into three groups according to resected margin status: no evidence of residual carcinoma (Negative group, n=96); carcinoma in situ at the bile duct stump (CIS group, n=10); and invasive carcinoma at any surgical marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 20 publications
7
59
1
Order By: Relevance
“…In 2005, Wakai et al26 reported that invasive carcinoma at the ductal resection margins had a strong adverse effect on survival in patients with extrahepatic cholangiocarcinoma, whereas residual carcinoma in situ did not. Thereafter, similar results were reported in Japan,27, 28, 29, 30, 31, 32, 33, 34, 35, 36 the USA,37 South Korea,38, 39 and Germany 40. These findings indicate that discrimination between carcinoma in situ and invasive carcinoma is critical when the ductal resection margins are found to be positive on intraoperative examination of frozen sections; residual carcinoma in situ may lead to late local recurrence, whereas residual invasive carcinoma results in early local recurrence 26…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…In 2005, Wakai et al26 reported that invasive carcinoma at the ductal resection margins had a strong adverse effect on survival in patients with extrahepatic cholangiocarcinoma, whereas residual carcinoma in situ did not. Thereafter, similar results were reported in Japan,27, 28, 29, 30, 31, 32, 33, 34, 35, 36 the USA,37 South Korea,38, 39 and Germany 40. These findings indicate that discrimination between carcinoma in situ and invasive carcinoma is critical when the ductal resection margins are found to be positive on intraoperative examination of frozen sections; residual carcinoma in situ may lead to late local recurrence, whereas residual invasive carcinoma results in early local recurrence 26…”
Section: Introductionsupporting
confidence: 83%
“…26, 27, 28, 31, 32, 34, 35, 38 The reported incidences of complete resection with histopathologically negative margins ranged from 69% to 87% 26, 27, 28, 31, 32, 34, 35, 38. All the studies included in Table 1 confirmed that ductal resection margin status was an independent prognostic factor in patients with extrahepatic cholangiocarcinoma.…”
Section: Biological Behavior Of Residual Carcinoma In Situmentioning
confidence: 80%
See 3 more Smart Citations